Glans ischemia in a 7-month-old boy who underwent correction of megaprepuce: case report and review of the literature - Kraske, Susanne; Müller, Fanny; Schellerer, Vera (Frontiers in Pediatrics, 2025)
Acute glans ischemia is a severe complication that can occur after penile surgery, such as circumcision, hypospadias repair, or disassembly of the corpora in epispadias. This rare condition is described in the current literature, especially after circumcision, although it is the less invasive procedure among those previously mentioned. We present a case of 7-month-old boy who developed glans ischemia after correction of megaprepuce. The condition was treated by intravenous unfractionated heparin. In our case, the complication of ischemia was complete dehiscence of the suture line at the coronal sulcus. Glans penis recovered completely and secondary intention wound healing occurred within 4 weeks. We reviewed the literature over the past 43 years (1981–2023) to describe the current options of surveillance, treatment, and outcome of glans ischemia after penile surgery in boys.